Equity Risk Premium in Lithuania’s Frontier Market: Integrating Country Risk and Market Drivers - Bonelli, Marco I. (Ekonomika, 2026)
This study quantifies Lithuania’s Equity Risk Premium (ERP) by integrating Damodaran’s country-risk premium (CRP) framework with a multiple regression on key market drivers. By using quarterly data from Q1 2015 to Q4 2024, the CRP model yields an implied cost of equity of 9.84%, corresponding to an ERP of 5.84% above a 4.00% U.S. risk-free rate. Our OLS regression explains 94% of ERP variation (adjusted R² = 0.94). Expected market return emerges as the strongest predictor (β = 0.914, p < 0.001), followed by sovereign bond yield (β = –0.602, p < 0.001) and inflation (β = –0.017, p = 0.025). Variance-inflation factors confirm that multicollinearity is not problematic. These results imply that targeted liquidity-enhancing reforms – such as market-making incentives – could compress Lithuania’s ERP by approximately 0.6 percentage points. By combining theoretical asset-pricing models with frontier-market empirics, our dual-lens approach offers actionable insights for policymakers and investors operating in structurally constrained equity markets.
Keywords: equity risk premium; country risk; Damodaran CRP model; Lithuania; regression analysis; market liquidity